THE WALK OF GODS AMONG MEN: Ratha Yatra and the theater of origins (DAPesquisa, 2025)
his article investigates the relationship between the notion  of performance proposed by Zeca Ligiéro in Teatro das Origens and practices carried out in Ratha Yatra festivals around Brazil and India. From the analysis of devotional practices, I suggest how we can, through the idea of ​​theater spectacle of communion, which takes place through dance, singing and rite, to understand the ways of perpetuating an ancient culture in current performativities.